Quo Vadis Perlindungan Hukum Pekerja Digital Lintas Batas Negara Sebagai Pekerja Migran - Nindry Sulistya Widiastiani (Fakultas Hukum Universitas Islam Indonesia, 2025)
This article analyses the legal status and protection of cross-border digital workers as migrant workers. Technological developments allow someone to work across borders without moving to another country. This phenomenon has led to a new trend, namely digital cross-border work. The legal status and legal protection within the framework of labour law also need to be studied. The research method used is normative legal research, using a statutory and conceptual approach. The analysis results show that there is no formal recognition or clear legal status of cross-border digital workers as migrant workers within the framework of employment law. This is based on a narrow interpretation that the indicator of the migrant worker category is doing work outside the territory of their country or carrying out physical migration. For this reason, building an inclusive and equitable work protection system for cross-border digital workers is necessary.